Review of the geometallurgical model for the estimation of mineral resources in porphyry copper deposits - Ramos Armijos, Nelson Jesús (2022)
The geometallurgical model is a tool that allows evaluating the necessity of mineral deposits from the geological, processing and production point of view. With this, it is possible to estimate the most realistic net present value and significantly reduce the technical-operational risk that occurs in the feasibility stages of a mining project. In the present investigation, an exhaustive search has been carried out on studies focused on geometallurgical modeling in porphyry copper deposits in which it has been estimated and simulated as geometallurgical total copper grade, oxide copper, penalizing elements, metallurgical recovery, bond work index and of abrasion. Through this research, it is evident that by incorporating geometallurgical attributes in the estimation of mineral resources, it is possible to better quantify the spatial variability of the deposit, anticipate those minerals that interfere in the metallurgical treatment and evaluate the probability of each destination for the mineral blocks in processing.